Pengaruh Extrinsic Reward terhadap Kepuasan Kerja Karyawan dengan Motivasi sebagai Variabel Mediasi (Studi pada Karyawan Restoran Mie Gacoan Surakarta) - R Rohwiyati (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2019)
The problem of this study that job satisfaction is declining, this is indicated by the high level of absenteeism and labor turnover. This research aims to analyses (1) significance effect of extrinsic reward on employee motivation (2) significance effect of extrinsic reward on employee job satisfaction (3) significance effect of motivation on employee job satisfaction (4) effect of extrinsic reward on employee job satisfaction, through motivation as mediating variable. This research using samples of 93 employee of the Mie Gacoan Restaurant in Surakarta city. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis using path analysis. Findings (1) extrinsic reward has significance effect on motivation, (2) extrinsic reward has significance effect on employee job satisfaction, (3) motivation has significance effect on employee job satisfaction, (4) motivation mediates the effect of extrinsic reward on employee job satisfaction. The contribution of this research can be used as a leadership policy to pay more attention to extrinsic rewards that can increase employee motivation and job satisfaction. This research can contribute to the development of human resource literature and as a reference for similar research.